Inhibitors of Amyloid Toxicity Based on β-sheet Packing of Aβ40 and Aβ42 - Takeshi Sato; Pascal Kienlen‐Campard; Mahiuddin Ahmed; Wei Liu; Huilin Li; James I. Elliott; Saburo Aimoto; Stefan N. Constantinescu; Jean‐Noël Octave; Steven O. Smith (2006)
Amyloid fibrils associated with Alzheimer's disease and a wide range of other neurodegenerative diseases have a cross β-sheet structure, where main chain hydrogen bonding occurs between β-strands in the direction of the fibril axis. The surface of the β-sheet has pronounced ridges and grooves when the individual β-strands have a parallel orientation and the amino acids are in-register with one another. Here we show that in Aβ amyloid fibrils, Met35 packs against Gly33 in the C-terminus of Aβ40 and against Gly37 in the C-terminus of Aβ42. These packing interactions suggest that the protofilament subunits are displaced relative to one another in the Aβ40 and Aβ42 fibril structures. We take advantage of this corrugated structure to design a new class of inhibitors that prevent fibril formation by placing alternating glycine and aromatic residues on one face of a β-strand. We show that peptide inhibitors based on a GxFxGxF framework disrupt sheet-to-sheet packing and inhibit the formation of mature Aβ fibrils as assayed by thioflavin T fluorescence, electron microscopy, and solid-state NMR spectroscopy. The alternating large and small amino acids in the GxFxGxF sequence are complementary to the corresponding amino acids in the IxGxMxG motif found in the C-terminal sequence of Aβ40 and Aβ42. Importantly, the designed peptide inhibitors significantly reduce the toxicity induced by Aβ42 on cultured rat cortical neurons.